Photoprotection in ethnic skin - Mohammed S. Al-Jamal; James L. Griffith; Henry W. Lim (Wolters Kluwer Medknow Publications, 2014)
Although cutaneous photodamage is partially mitigated by darker skin pigmentation, sun-induced aging, dyspigmentation, sunburns, and skin cancers are reported worldwide in all skin types and races. The severity of photodamage varies from individual to individual, and is predominantly based upon genetic differences altering the body's response or susceptibility to sun damage. In addition, non-Caucasian patients are less likely to perform skin self-examinations, attend dermatologic follow-ups, and seven times less likely to apply sunscreen than Caucasian patients. Therefore, the remainder of this article will discuss the categories of photoprotective agent [environmental, biologic, physical, and UV filters, i.e., sunscreens] as well as the topics of photoaging, dyspigmentation, photocarcinogenesis, and the controversy surrounding vitamin D deficiency from photoprotection in the context of ethnic skin.